Biophysical characterization and molecular phylogeny of human KIN protein - Pattaro Junior, Jose Renato; Caruso, Icaro Putinhon [UNESP]; Lima Neto, Quirino Alves de; Duarte Junior, Francisco Ferreira; Rando, Fabiana dos Santos; Marques Gerhardt, Edileusa Cristina; Fernandez, Maria Aparecida; Vicente Seixas, Flavio Augusto (Springer, 2019)
The DNA/RNA-binding KIN protein was discovered in 1989, and since then, it has been found to participate in several processes, e.g., as a transcription factor in bacteria, yeasts, and plants, in immunoglobulin isotype switching, and in the repair and resolution of double-strand breaks caused by ionizing radiation. However, the complete three-dimensional structure and biophysical properties of KIN remain important information for clarifying its function and to help elucidate mechanisms associated with it not yet completely understood. The present study provides data on phylogenetic analyses of the different domains, as well as a biophysical characterization of the human KIN protein (HSAKIN) using bioinformatics techniques, circular dichroism spectroscopy, and differential scanning calorimetry to estimate the composition of secondary structure elements; further studies were performed to determine the biophysical parameters Delta H-m and T-m. The phylogenetic analysis indicated that the zinc-finger and winged helix domains are highly conserved in KIN, with mean identity of 90.37% and 65.36%, respectively. The KOW motif was conserved only among the higher eukaryotes, indicating that this motif emerged later on the evolutionary timescale. HSAKIN has more than 50% of its secondary structure composed by random coil and beta-turns. The highest values of Delta H-m and T-m were found at pH 7.4 suggesting a stable structure at physiological conditions. The characteristics found for HSAKIN are primarily due to its relatively low composition of alpha-helices and beta-strands, making up less than half of the protein structure.
Keywords: KIN (Kin17) protein; Phylogeny; Circular dichroism; DSC analysis; Tumor marker